COMMISSIVE ILLOCUTIONARY SPEECH ACT OF TRADERS' SPEECH IN WIYONO MARKET, PESAWARAN, AND ITS IMPLICATION TOWARD THE LEARNING OF BAHASA INDONESIA IN SENIOR HIGH SCHOOL - Iqbal Hilal; Atik Kartika; Endah Dina Atiqoh (Universitas Lampung, 2022)
The focus of this research discusses the types of commission illocutionary speech acts in the speech of traders at the Wiyono Market, Pesawaran and their interactions with Indonesian Language learning in high school. In this regard, this study aims to describe the types of commission illocutionary speech acts in the speech of traders at the Wiyono Market, Pesawaran and their interactions in Learning Indonesian in high school.The method used in this study is a qualitative description. The source of data in this study is the speech of traders at the Wiyono Market, Pesawaran. Data collection techniques used are observation, observation, and recording.The results of this study indicate that there are commissive illocutionary speech acts in Pasar Wiyono Pesawaran which include commissive illocutionary speech acts of vowing function consisting of two data, commissive illocutionary speech acts of promised function consisting of seventeen data, and commissive speech acts of offering function consisting of sixteen data.Fokus penelitian ini membahas jenis-jenis tindak tutur ilokusi komisif pada tuturan pedagang di Pasar Wiyono Pesawaran dan implikasinya terhadap pembelajaran Bahasa Indonesia di SMA. Sehubungan dengan itu, penelitian ini bertujuan untuk mendeskripsikan jenis-jenis tindak tutur ilokusi komisif pada tuturan pedagang di Pasar Wiyono Pesawaran dan implikasinya pada pembelajaran Bahasa Indonesia di SMA.Metode yang digunakan pada penelitian ini ialah deskriptif kualitatif. Sumber data dalam penelitian ini ialah tuturan pedagang di Pasar Wiyono Pesawaran. Teknik pengumpulan data yang digunakan yaitu teknik pengamatan, simak catat, dan perekaman.Hasil penelitian ini menunjukkan bahwa terdapat tindak tutur ilukosi komisif di Pasar Wiyono Pesawaran yang meliputi tindak tutur ilokusi komisif fungsi berkaul terdiri atas dua data, tindak tutur ilokusi komisif fungsi menjanjikan terdiri atas tujuh belas data, dan tindak tutur ilokusi komisif fungsi menawarkan terdiri atas enam belas data.Keywords: commissive speech acts, vows, offers, and promisesDOI Artikel: https://doi.org/10.23960/J-Simbol/v10i1.2022.01